Influence of Intercalation Cobalt on Properties of Layered Crystals In2Se3 - V.B. Boledzyuk; A.D. Shevchenko; Z. R. Kudrynskyi (Журнал нано- та електронної фізики)
Influence intercalation ions of Co2 + on properties of monocrystals In2Se3 was investigated. It is shown that cobalt intercalation in In2Se3 leads to decrease of a constant lattice in a direction perpendicular to a base plane of a crystal, leaving thus invariable structural type of investigated samples. A ferromagnetism was established in Co0.15In2Se3 intercalates, obtained by intercalation in a magnetic field. The dependence of the magnetic moment cobalt intercalates In2Se3 on the strengths of the magnetic field has a view of a hysteresis loop.